Eocene to Quaternary Deformation of the Southern Puna Plateau: Thermochronology, Geochronology, and Structural Geology of an Andean Hinterland Basin (NW Argentina). Issue 6 (16th June 2022) - McMillan, Mitchell; Schoenbohm, Lindsay M.; Tye, Alexander; McMillan, Malcolm F.; Zhou, Renjie
Abstract: Cordilleran orogens are complex tectonic systems, strongly influenced by lithospheric deformation and exhumation. However, in the type region of the Central Andes, the timing and mechanisms of deformation and mountain building remain poorly constrained, especially for the high‐elevation Puna Plateau of NW Argentina. We use geologic mapping, structural cross‐sections, low‐temperature thermochronology, and U‐Pb dating of ash and detrital zircons to elucidate the history and style of orogenic deformation in the Antofalla region of the Puna Plateau. Cooling ages of major reverse fault hanging walls and dated growth strata indicate that crustal shortening activated major reverse faults during the Eocene and continued out‐of‐sequence through the Early Miocene. This protracted period of shortening, which resulted in the filling of the Antofalla Basin, was followed by a transient episode of upper‐crustal E‐W extension on a major normal fault system during the Late Miocene. Pliocene to Quaternary time saw E‐W shortening return to the region. Our structural cross‐section permits only a low magnitude of shortening (∼15–25%), which stands in contrast to the 60‐km thick crust. Triassic to Cretaceous cooling ages from footwall rocks and minor structures indicate that the entire region experienced little exhumation or sedimentation during the Mesozoic, perhaps retaining a crust thickened during multiple episodes of Paleozoic orogenesis. The crust may also reflect lower‐crustal thickening due to the growth of a lithospheric drip during the Late Miocene. Key Points: Combination of structural mapping, thermochronology, and U‐Pb chronostratigraphy reveals four phases of Cenozoic deformation Exhumation due to horizontal shortening was underway by the Eocene (∼45 Ma), ∼20 Myr earlier than previously inferred for the region Shortening propagated out‐of‐sequence, westward from the Calalaste Range into the Antofalla Basin until ∼15 Ma